The “Lost Literature” of Student-Athlete Services: A Content Analysis of Academic Athletic Journal Articles from 1985 to 2006 - Rubin, Lisa M. (Sage, 2025)
The National Advisor/Academic Athletic Journal was published by the National Association of Academic and Student-Athlete Development Professionals (N4A) from the early 1980s to 2006. Scholarship in the student-athlete services field was “lost” because it was only available in print to members. Much of this literature has been unread and uncited. Thirty-one issues published from 1985 to 2006 were collected and digitized to preserve and share in an open-access repository. A content analysis was conducted on 168 items over 22 years to understand the topics and trends in this missing literature, the foundation for the field of student-athlete services. The journal published 99 empirical articles and 69 gray literature items in this time frame. Sharing these articles allows 241 unique authors to receive credit for their work in future research. Findings show many current issues affecting college athletes and student-athlete services professionals were prevalent in the journal’s issues. Implications for policy and suggestions for future research were presented.
Keywords: content analysis; student-athlete services; student development; career development; research utilization; higher education